Investigation of Phytochemicals and Inflammatory Response Modulation by Himalayan Orchid Root Extract - P Duhijod, Karishma; Tiwari, Priyanka; Priyanga, J.; A, Ramya; Sharma, Vijay; F Mehta, Farhad; Manda, Ram Mohan; J, Monisha (Journal of Neonatal Surgery, 2025)
Inflammations is body’s natural physiological response that helps the body to protect the mechanism of the body from harmful agents and supports tissue repair. However, when prolonged or unregulated, it can lead to chronic conditions such as cardiovascular disorders, osteoarthritis, and neurodegenerative diseases. Although conventional anti-inflammatory drugs like NSAIDs and corticosteroids are effective, their long-term use is often associated with adverse side effects. This research investigates the soothing effect on inflammation of water-ethanol base extract obtained from the root system of Dactylorhiza hatagirea and the rhizome of Curcuma angustifolia rhizomes, both traditionally used in Indian and Nepalese medicine. The plant materials were authenticated and extracted using a hydro-ethanolic solvent, followed by phytochemical screening that confirmed the presence of major bioactive constituents, including flavonoids, phenolics, saponins, and carbohydrates. Quantitative analysis demonstrated notable concentrations of total phenolics (21.25 mg GAE per 100 mg of plant extract), flavonoids (33.82 mg of QE per 100 mg of plant extract) and tannins (12.83 mg/mL TAE per 100 mg of plant extract). Anti-inflammatory response is studied using Carrageenan induced paw model in wistar rats. Both extracts showed a dose-dependent reduction in paw swelling, with Curcuma angustifolia producing up to 55.3% inhibition and Dactylorhiza hatagirea showing 52.9% inhibition at 200 mg/kg, compared to 66.8% for the standard drug, diclofenac sodium. Protein denaturation assay is carried out to assess invitro anti-inflammatory activity, showed concentration dependent inhibition, with Dactylorhiza hatagirea and Curcuma angustifolia extracts exhibiting maximum inhibition of 78.4% and 72.1% at 400 µg/mL, respectively, compared to 85.6% by diclofenac sodium. Additionally, herbal tablets were formulated using the active extracts and evaluated as per Indian Pharmacopoeia guidelines. The study demonstrates that both plant extracts possess notable anti-inflammatory activity, likely due to their rich phytochemical content. These results shows that the cultural medicinal use of these plants and indicate their potential as natural sources for developing anti-inflammatory therapies with potentially fewer side effects than conventional drugs.